An anti‐oxidative cell culture dish inhibits intracellular reactive oxygen species accumulation and modulates pluripotency‐associated gene expression in mesenchymal stem cells. Issue 5 (4th March 2020) - Ikeda, Yutaka; Inuzuka, Naoki; Goto, Mitsuaki; Akaike, Toshihiro; Nagasaki, Yukio
Abstract: Maintenance of the pluripotent state of mesenchymal stem cells (MSCs) during in vitro expansion is an important factor for the successful proliferation of MSCs possessing high differentiation capacity. However, the differentiation potential of MSCs can easily be lost during in vitro expansion, particularly at late passages. Reactive oxygen species (ROS) are signaling molecules that help to maintain MSC function; however, excessive ROS generation can induce senescence and impair both the differentiation capacity and proliferation of MSCs. In this study, we have designed an amphiphilic block copolymer (redox copolymer), which possesses ROS scavenging capacity in the hydrophobic site. When this redox copolymer was coated on cell culture dishes coupled with human E‐cadherin chimeric antibody (hE‐cad‐Fc), it had an antioxidative effect on cultured MSCs. We also confirmed that the redox polymer construct poly(ethylene glycol) tethered chain on the surface prevented nonspecific cell binding, whereas the co‐immobilized surface allowed high adhesion of E‐cadherin‐positive MSCs. Interestingly, the intracellular ROS level was significantly decreased by the prepared cell culture dish, despite ROS being scavenged only on the surface of the dish, on the cell exterior. Consequently, the cultured MSCs retained high expression levels of pluripotency‐associated genes, including SOX2.